DIFFERENCES IN SELF-ESTEEM IN ADOLESCENTS WITH INTACT AND BROKEN HOMES - Chelsea Rizky Valentine; Annisa Nasywa Kalyca; Risma Anita Puriani (Journal of Social and Economics Research, 2026)
Self-esteem represents an individual’s evaluative judgment of personal worth and competence and constitutes a critical element in adolescent psychological development. Variations in family structure, particularly between intact and non-intact families, are assumed to influence the formation of adolescents’ self-esteem. This study aimed to examine differences in self-esteem levels among adolescents aged 11–19 years originating from these two family backgrounds using a quantitative approach with a comparative design. Participants were selected through purposive sampling, and data were collected using the Coopersmith Self-Esteem Inventory (CSEI). Comparative statistical analysis was applied to determine whether significant differences existed between groups. The findings indicated that adolescents from non-intact families tended to exhibit lower self-esteem than those from intact families, with disparities observed in perceived strengths, sense of importance, kindness, and abilities. These results suggest that family integrity contributes substantially to the development of adolescent self-esteem, underscoring the importance of familial and environmental support in enhancing self-confidence, particularly for adolescents from broken families.